From waste Coca Cola® to activated carbons with impressive capabilities for CO2 adsorption and supercapacitors - Boyjoo, Y.; Cheng, Y.; Zhong, H.; Tian, H.; Pan, J.; Pareek, Vishnu; Jiang, S.; Lamonier, J.; Jaroniec, M.; Liu, J. (Pergamon, 2017)
We herein report the synthesis of heteroatoms doped, high surface area microporous activated carbons (AC) by utilisation of Coca Cola® as a potential source of waste biomass, for applications as CO2 adsorbent and electrodes of supercapacitors. N, S dual doped carbon spheres are firstly obtained by hydrothermal treatment of Coca Cola® and then thermally activated by either KOH or ZnCl2. The resulting KOH activated carbon material (CMC-3) exhibits extremely high adsorption capability for CO2 with 5.22 mmol g-1 at 25 °C and 1 atm, one of the highest values ever recorded for a carbonaceous material. On the other hand, ZnCl2 activated carbon material (CMC-2) performs excellently as an electrode for supercapacitor, exhibiting very high specific capacitance of 352.7 F g-1 at a current density of 1 A g-1 in 6 M KOH electrolyte, which again is one of the highest values recorded for a biomass derived AC. Coca Cola® has high content in carbon as sugars, provides in-situ doping of O, N and S and has constant composition, as opposed to other conventional biomass materials, making it an attractive and cheap alternative for synthesis of high performance AC for environmental and energy storage purposes.